Professional Training of Engineering Teachers - Gupta, B. L. (Journal of Engineering Education Transformations, 1994)
The paper highlights the importance of professional training of engineering teachers. A strategy of training needs assessment at in institutional level, occupation level and individual level has been described. Two models for training have been described for in service training of teachers and pre-service training of potential teachers. Significant issues for making the training relevant and reliable are discussed.